The EFFECT OF PROBLEM-BASED LEARNING MODEL ON STUDENTS' SCIENCE LITERACY SKILLS IN CLASS VII ECOLOGY MATERIAL IN PUBLIC JUNIOR HIGH SCHOOL 27 MEDAN - Natasya, Titania; Hardinata, Aristo (Universe, 2024)
This research aims to investigate the influence of the Problem Based Learning (PBL) model on the science literacy skills of seventh-grade students in ecology subject at SMP Negeri 27 Medan. The research method employed was quantitative with a sample of 64 students from classes VII-6 and VII-5, selected using purposive sampling technique. The instrument used was a science literacy test, with the independent variable being the teaching model (PBL and direct instruction) and the dependent variable being the students' science literacy skills. The results of the research indicate that the implementation of the PBL model has a significant influence on the science literacy skills of seventh-grade students in class VII-6. Initially, the science literacy skills of students in class VII-6 were at level 2 with a score of 37.50, classified as insufficient. However, after the implementation of the PBL model, the science literacy skills increased to level 4 with a score of 69.58, classified as sufficient. In conclusion, the application of the PBL model was effective in improving the science literacy skills of students in ecology subject at class VII-6 of SMP Negeri 27 Medan. This finding provides important implications for the development of problem-oriented learning approaches to enhance students' science literacy.